Home Monitoring for Cardiovascular Implantable Electronic Devices: Benefits to Patients and to Their Follow-up Clinic. (October 2015) - Leahy, Robin A.; Davenport, Elizabeth E.
Abstract : Recent technological advances in the management of patients with cardiovascular implantable electronic devices (CIEDs) have expanded clinicians' ability to remotely monitor patients with CIEDs. Remote monitoring, in addition to periodic in-person device evaluation, provides many advantages to patients and clinicians. Aside from the therapeutic and diagnostic benefits of pacemakers, implantable cardioverter-defibrillators, cardiac resynchronization therapy devices, and implantable loop recorders, improvement in clinical outcomes, clinical efficiencies, and patient experience can be realized with the adoption of remote CIED monitoring. These advantages create significant value to both patients and CIED follow-up centers.